Properties of wood relating to stacking and defects of timber in kiln drying / Mohd Junaidi Mohamad - Mohamad, Mohd Junaidi (2001)
Wood must be dried before use. The methods in dry kiln are important. In stacking the timber, sticker in correct location will influence proper drying to produce good timber. The location of sticker that is not of uniform thickness and an unequally in stacking are causes to wood warping beside an unequal air circulation to the timber. The good air circulation in kiln influenced the rate of moisture content decrease without effected to the timber.